1992
DOI: 10.1111/j.1600-0528.1992.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of posterior approximal caries incidence with consumption of sweets with regard to other caries‐related factors in15–18‐year‐olds

Abstract: The aim of this study was to analyze the relationships between caries incidence and a number of caries-related factors in 15-18-yr-olds, in order to estimate the explanatory value of consumption of sweets under different conditions. Sixty-nine 18-yr-olds were interviewed about consumption of sweets and other sugar-containing products during the past 3 yr. Data on oral hygiene, salivary counts of mutans streptococci and lactobacilli, salivary flow rate and oral sugar clearance time were collected when the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
2
15
0
4
Order By: Relevance
“…Bjarnason et al 87 in a detailed dietary study of 12±13 year-olds in Iceland showed that there was a higher incidence of caries surfaces with frequent intake of buns and cakes with meals and confectionery. These findings were confirmed in a 3 year longitudinal study of Swedish 15±18 year olds 88 . The correlation between sweet consumption and the incidence of posterior approximal caries was 0.25.…”
Section: Relationship Between Frequency and Amount Of Sugar Intake Ansupporting
confidence: 72%
“…Bjarnason et al 87 in a detailed dietary study of 12±13 year-olds in Iceland showed that there was a higher incidence of caries surfaces with frequent intake of buns and cakes with meals and confectionery. These findings were confirmed in a 3 year longitudinal study of Swedish 15±18 year olds 88 . The correlation between sweet consumption and the incidence of posterior approximal caries was 0.25.…”
Section: Relationship Between Frequency and Amount Of Sugar Intake Ansupporting
confidence: 72%
“…These findings are in accordance with Sundin et al (23) who also found a weak or non-existent relationship between these variables. However, Ravald and Birkhed (20) demonstrated that individuals with low salivary flow rate have a higher predisposition to cariogenic activity.…”
supporting
confidence: 93%
“…Sundin 91 monitored caries development in a group of Swedish children from repeated cross-sectional data and found a strong correlation between caries increment and the consumption of sweets. The relationship was strongest for those with poor (þ0.51) compared with good oral hygiene (þ 0.11).…”
Section: Human Intervention Studiesmentioning
confidence: 99%
“…A higher caries incidence was associated with consumption of sweets and cakes at mealtimes and with frequency of confectionery consumption. In a study of longitudinal design, Sundin et al 91 found that frequency of consumption of sweets was an important caries-related factor in Swedish teenagers. Caries incidence over a 3 year period was significantly related to frequency of intake of confectionery (r ¼ þ0.25) and the relationship was stronger for teenagers with poor oral hygiene and a low salivary flow rate (r ¼ þ0.7).…”
mentioning
confidence: 99%